Crystallization of Santri's Religious Attitudes through the Pesantren Cultural Process - Mahlil Nurul Ihsan (Syntax Corporation Indonesia, 2021)
Each pesantren culture has a unique variation in shaping the religious attitudes of students, this problem was initially caused by the weakness of the pesantren culture which caused the moral decadence of students, so that the process of pesantren culture had to be strengthened. This type of research uses qualitative field research with descriptive methods and data collection techniques using interviews, documentation, and observation. The results of this study explain the cultural process of the modern Al-Aqsho Islamic boarding school, Sumedang Regency, consisting of religious socialization, modernity, moderation, adaptation emphasizing modern life systems, habituation which is applied more to the habituation of the grantor system and enculturation showing modern pesantren culture. Meanwhile, the cultural process of Al-Ittifaq Islamic Boarding School in Bandung Regency consists of religious socialization, entrepreneurship, and society, adaptation emphasizing the adaptation of religious experiences, adaptation highlighting the social life system of the community, adaptation to the entrepreneurial work environment, habituation applied to the religious system, community and entrepreneurship and enculturation shown religious agribusiness pesantren culture.